Maternal prepregnancy body mass index and risk of preterm birth: the role of weight gain during pregnancy, race, and ethnicity - Sawadogo, Wendemi; Tsegaye, Medhin; Gizaw, Andinet; Newland, Hunter; Adera, Tilahun (American Journal of Perinatology, 2024)
Objective Preterm birth (PTB) is one of the leading causes of infant and neonatal mortality. Prepregnancy body mass index (BMI; kg/m2) has been linked to PTB but the evidence of this association by weight gain during pregnancy, race, and ethnicity is limited. This study aimed to assess the association between maternal prepregnancy BMI and PTB stratified by weight gain during pregnancy, race, and ethnicity. Study Design The U.S. natality data from 2017 to 2021 were used. In this analysis, we included mothers who had a live singleton birth and available data for prepregnancy BMI, gestational age at birth, weight gain during pregnancy, race, and ethnicity. Logistic regression models were used to assess the association between prepregnancy BMI categories and PTB stratified by weight gain during pregnancy, race, and ethnicity. Results A total of 17,311,509 singleton live births were included of which 1,393,889 (8.05 %) were PTBs. After adjusting for confounders, compared with normal prepregnancy BMI mothers (18.5–24.9), those with underweight BMI (<18.5) were at increased odds of PTB regardless of weight gain during pregnancy, race, and ethnicity. However, for mothers with a prepregnancy BMI above the normal weight (≥25), the association between prepregnancy BMI and PTB differs by weight gain during pregnancy, race, and ethnicity. Asian mothers with obesity II (35.0–39.9) had 93% (odds ratio [OR] = 1.93, 95% confidence interval [CI]: 1.62–2.30) increased odds of PTB for weight gain during pregnancy of 31 to 40 pounds. Their White, Hispanic, and Black counterparts experienced lower odds of PTB for similar weight gain during pregnancy (White: OR = 1.56, 95% CI: 1.51–1.60; Hispanic: OR = 1.48, 95% CI: 1.41, 1.54; and Black: OR = 1.22, 95% CI: 1.17–1.27). Conclusion Mothers with underweight BMI were at increased risk of PTB regardless of weight gain during pregnancy, race, and ethnicity. However, the association between high prepregnancy BMI and PTB varied by weight gain during pregnancy, race, and ethnicity. Key Points
Keywords: body mass index; dept.pch; ethnicity; obesity; peer-reviewed; pregnancy; preterm birth; race; weight gain during pregnancy

Black fathers' views on breastfeeding facilitators, barriers, and support services: Insights from a qualitative community-based participatory research study - Rios, Jasmine; Frieson, Tomeka; Ray, Natasha; Edwards, Doug; Pérez-Escamilla, Rafael; O'Connor Duffany, Kathleen (Maternal & Child Nutrition, 2024)
Despite the persistence of breastfeeding racial and ethnic disparities in the United States, little is known about Black fathers' perceptions of breastfeeding and breastfeeding support services (e.g., maternity hospital-based care and lactation management care). This qualitative, community-based participatory research study reports Black fathers' perceptions of barriers and facilitators to breastfeeding, including the provision of breastfeeding support services in Connecticut. A focus group guide was co-developed with community partners and adapted from the Barrier Analysis Tool to identify breastfeeding facilitators, barriers, and service improvement areas. Four focus groups were conducted with 30 Black fathers who were Connecticut residents with a child under 3 years old. Qualitative data were analyzed using rapid template analysis involving deductive and inductive coding. We identified factors influencing breastfeeding and fathers' ability to support breastfeeding across all levels of the Socio-Ecological Model. Facilitators included high paternal breastfeeding knowledge, paternal breastfeeding involvement, parents' shared decision-making, extensive maternity hospital discharge support, ongoing breastfeeding support into the postnatal period, availability of community breastfeeding resources, and designated spaces for public breastfeeding. Barriers included low paternal breastfeeding knowledge, familial discouragement, insufficient prenatal breastfeeding education, exclusion of the father from breastfeeding support services, and stigma against breastfeeding in public. Understanding breastfeeding perceptions among members of a mother's support network, including their partners, is key for developing effective person- and family-centered breastfeeding education and counseling services that are well coordinated from the prenatal to postnatal periods with strong direct engagement from fathers.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/mcn.13776
Keywords: dept.pch; peer-reviewed

Insomnia symptoms and the risk of all-cause mortality among stroke survivors - Sawadogo, Wendemi; Adera, Tilahun; Alattar, Maha; Perera, Robert; Burch, James (BMC Public Health, 2024)
Insomnia is more frequently reported in stroke survivors but its independent role in mortality in stroke survivors is unknown. The purpose of this study was to investigate the association of insomnia symptoms with all-cause mortality among stroke survivors.
Keywords: Age difference; All-cause mortality; Insomnia symptoms; Sex difference; Stroke survivors; dept.phc; peer-reviewed

Love, support and structural holes: Maori ̄ whanau ̄ carer experiences in collective family care systems - Simpson, M.L.; McAllum, K.; Fox, S.; Unson, C.; Hancock, T.O.; Carlson, A. (Ageing and Society, 2024)
As the population of Aotearoa New Zealand ages, informal family carers will play an increasingly important role in caring for older adults at home. Multi-generational living arrangements are a growing trend, particularly among Māori communities, where caring for older relatives within the family home is widespread. This article uses in-depth, semi-structured interviews with Māori whānau (extended family members) caring for kaumātua (older family members) at home to explore how carers experienced care coordination in the broader care collective. The findings centred on three interconnected factors that described the collective organisation of care: (1) whānau care as normal; (2) whānau care as collective coordination; and (3) whānau carer knowledge and needs as unseen. The findings show that although whānau care of kaumātua is highly valued, ‘structural holes’ within care systems contribute to challenges in care coordination. Despite extensive whānau support for kaumātua, primary carers often felt that their knowledge, preferences and self-care needs remained unseen and not translatable to those outside the everyday care situation. Rather than assuming an artificial binary difference between ‘collective’ and ‘individually oriented’ care contexts and cultures, analysing the cultural norms surrounding whānau care-giving confirms that collective care system members face similar and different challenges to carers with smaller caring capacities. © The Author(s), 2024.
Keywords: care collectives; care networks; dept.pch; family care; older Maori; older people; peer-reviewed

Insomnia symptoms and increased risk of all-cause mortality by age and sex - Sawadogo, W.; Adera, T. (Journal of Clinical Sleep Medicine, 2024)
Study Objectives: Prior research suggests that insomnia may increase the risk of death. However, the potential influence of age and sex is unclear. This study aimed to investigate the association of insomnia symptoms with all-cause mortality by age and sex. Methods: This prospective cohort was drawn from the Health and Retirement Study, a survey of Americans older than 50 years and their spouses of any age from 2002–2018. Insomnia symptom scores were based on difficulties initiating sleep, difficulty maintaining sleep, waking up too early, and nonrestorative sleep. Cox proportional-hazards regression models were employed to investigate the association between insomnia symptoms and all-cause mortality stratified by age and sex. Results: A total of 33,004 participants were included with a mean age of 61.7 years and 56.8% females. Over a mean follow-up of 8.4 years, 8,935 (27.1%) deaths were recorded. After adjusting for confounding, males with insomnia symptom scores ranging from 5–8 had a 71% increased risk of death (hazard ratio = 1.71; 95% confidence interval: 1.27, 2.30) compared with their counterparts without insomnia symptoms. Similarly, males aged ≥ 60 years and females aged < 60 years with insomnia symptoms ranging from 5–8 had an increased risk of death compared with their counterparts without insomnia symptoms (hazard ratio = 1.15; 95% confidence interval: 1.02, 1.31 and hazard ratio = 1.38; 95% confidence interval: 1.00, 1.90, respectively). However, there was no increased risk of death for females aged ≥ 60 years (hazard ratio = 0.94; 95% confidence interval: 0.84, 1.06). Conclusions: These findings suggest that insomnia symptoms may serve as predictors of low life expectancy. © 2024 American Academy of Sleep Medicine. All rights reserved.
Keywords: age difference; all-cause mortality; dept.pch; insomnia symptoms; peer-reviewed; sex difference

Addressing college student food insecurity: grocery pickup program needs assessment - Neal, L.; Anziano, J.; Zigmont, V.A. (Journal of Hunger and Environmental Nutrition, 2024)
Food insecurity is a detriment to the health and academic success of college students nationwide, increasing the need for innovative interventions. This cross-sectional study administered an online survey to 140 students attending a Northeastern public university to understand student interest in a student-sustained grocery program. The majority of students (53.6%) were food insecure (FI), measured with the USDA 6-item survey, as well as upperclassmen. Results identified that FI students may be most interested in a food pickup program that provides them with cooking classes, snack foods, and ingredients for 2–6 meals at a cost between $24.50 and $26.90 per week. © 2024 Taylor & Francis Group, LLC.
Keywords: Food insecurity; college students; dept.pch; food assistance; grocery; peer-reviewed

The impact of social isolation policies during COVID-19 on suburban mothers and pregnant women with opioid use disorder - Lamonica, Aukje; Boeri, Miriam; Khan, Mishal (Women & Health, 2024)
The aim of this qualitative research paper was to identify how social isolation policies implemented during the COVID-19 pandemic impacted the lives of pregnant women and mothers with opioid use disorder. Between 2020 and 2022, in-depth interviews were conducted with 37 mothers and pregnant women living in the suburbs of Newark, NJ, and New Haven, CT. Participants had to be at least 18 years old, misused or abused opioids in the last 12 months while residing in a suburban location, and pregnant or caring for children aged 12 and younger. We used syndemics theory to guide our grounded theory analysis to identify relationships between social situations, health conditions, and opioid use disorder. Five major themes emerged that were either directly or indirectly impacted by social isolation caused by policies implemented during the COVID-19 pandemic: Relationships, Environment, Services, Drug Use, and Health. Findings from this study reveal new insights into how mothers and their health were impacted by prolonged social isolation policies and offer suggestions for policymakers and service providers to better address future crisis.
_eprint: https://doi.org/10.1080/03630242.2024.2377640
Keywords: COVID-19; dept.pch; mothers; opioid use disorder; peer-reviewed; social isolation policy

Racial and ethnic disparities in cancer occurrence and outcomes in rural United States: a scoping review - Njoku, Anuli; Sawadogo, Wendemi; Frimpong, Princess (Cancer Control, 2024)
BackgroundCancer is the second-leading cause of death in the United States. Most studies have reported rural versus urban and Black versus White cancer disparities. However, few studies have investigated racial disparities in rural areas.ObjectiveWe conducted a literature review to explore the current state of knowledge on racial and ethnic disparities in cancer attitudes, knowledge, occurrence, and outcomes in rural United States.MethodsA systematic search of PubMed and Embase was performed. Peer-reviewed articles published in English from 2004-2023 were included. Three authors independently reviewed the articles and reached a consensus.ResultsAfter reviewing 993 articles, a total of 30 articles met the inclusion criteria and were included in the present review. Studies revealed that underrepresented racial and ethnic groups in rural areas were more likely to have low cancer-related knowledge, low screening, high incidence, less access to treatment, and high mortality compared to their White counterparts.ConclusionUnderrepresented racial and ethnic groups in rural areas experienced a high burden of cancer. Improving social determinants of health may help reduce cancer disparities and promote health.
Keywords: dept.pch; peer-reviewed

Utilizing Local Professional Association Chapters as Pathways for Leadership Development - Batista, Nicole; Risisky, Deb; Lutz, Tara M.; Clinesmith, Ellen; Morgan, Jahkeeva (Health Promotion Practice, 2024)
In 2019, there was no entity specifically dedicated to health promotion and education practitioners in Connecticut or New England. This made it difficult for health promotion practitioners and students to network, collaborate, and engage in professional development. The purpose of this article is to share our experiences developing the new Connecticut Chapter of the Society for Public Health Education (CT SOPHE), including how we leveraged student interns during the first two years to promote organizational growth. To build our membership, it was important to determine who would be interested in joining CT SOPHE and so we focused on three groups: the current workforce/professionals, future workforce/students, and future leaders/interns. Over the course of these two years, three interns were recruited to help with creating a needs assessment (MPH student) and program development (two BS students); the organization was established by an MPH student as her internship project. Three former interns share how their experience working with the CT SOPHE board has helped them develop crucial leadership skills early in their careers. Embedding student interns into the framework and operations of CT SOPHE demonstrates an intentional and strategic commitment to the sustainability of both the organization and the workforce.
Keywords: dept.pch; peer-reviewed

Understanding food insecurity among collegiate athletes: a qualitative study at a public university in New England - Anziano, Jennifer; Zigmont, Victoria A. (Journal of Athletic Training, 2024)
Context: Authors of previous research at a public university in New England, where the current study takes place, showed that approximately one-third of undergraduate students have experienced some aspect of food insecurity. More recent investigators at this university revealed that students who were members of a sport team were 4 times more likely to be food insecure than their peers who were not on a sport team. The estimated prevalence of student-athlete food insecurity from other previous research studies ranged from 14% to 32%. Objective: To understand the contributing factors to food insecurity among collegiate athletes. Design: Qualitative study. Setting: A public university in New England. Patients or Other Participants: Data are presented for 10 collegiate athletes who experienced some level of food insecurity according to the United States Department of Agriculture Six-Item Short Form. Data Collection and Analysis: Data were collected using a brief demographic questionnaire and semistructured interviews. Results: Contributing factors were a lack of time, special dietary needs, limited campus dining options, and limited access to transportation or kitchens. Coping strategies were managing time and resources, buying cheaper foods, and skipping meals. Food insecurity negatively affected students' athletic performance. The athletes struggled to balance their athletic and academic schedules and obtain a diet that allowed them to meet their performance goals. Conclusions: Additional and innovative programming is needed to support food-insecure student-athletes. © by the National Athletic Trainers' Association, Inc.
Keywords: academic performance; athletic performance; dept.pch; diet; nutrition; open-access; peer-reviewed

Perceptions of racial-ethnic inequities in COVID-19 healthcare and willingness to receive the COVID-19 vaccine - Sherchan, J.S.; Fernandez, J.R.; Njoku, A.; Brown, T.H.; Forde, A.T. (Epidemiology, 2024)
Background: Perceptions of the US healthcare system can impact individuals' healthcare utilization, including vaccination intentions. This study examined the association between perceived racial-ethnic inequities in COVID-19 healthcare and willingness to receive the COVID-19 vaccine. Methods: This study used data from REACH-US, a nationally representative online survey of a large, diverse sample of U.S. adults (N=5145 January 26, 2021-March 3, 2021). Confirmatory factor and regression analyses examined a latent factor of perceived racial-ethnic inequities in COVID-19 healthcare, whether the factor was associated with willingness to receive the COVID-19 vaccine, and whether associations varied across racial-ethnic groups reported as probit estimates (B) and 95% confidence intervals (CIs). Results: Perceived racial-ethnic inequities in COVID-19 healthcare were highest among Black/African American adults (mean latent factor score: 0.65 ± 0.43) and lowest among White adults (mean latent factor score: 0.04 ± 0.67). Black/African American (B = -0.08; 95% CI = -0.19, 0.03) and Native Hawaiian/Pacific Islander (B = -0.08; 95% CI = -0.23, 0.07) adults who perceived greater racial-ethnic inequities in COVID-19 healthcare were less willing than participants who perceived lower inequities. In contrast, American Indian/Alaska Native (B = 0.15; 95% CI = -0.01, 0.30), Asian (B = 0.20; 95% CI = 0.08, 0.31), Hispanic/Latino (English language preference) (B = 0.22; 95% CI = 0.01, 0.43), Multiracial (B = 0.23; 95% CI = 0.09, 0.36), and White (B = 0.31; 95% CI = 0.19, 0.43) adults who perceived greater racial-ethnic inequities in COVID-19 healthcare were more willing to receive the COVID-19 vaccine than participants perceiving higher inequities. Conclusions: Greater perceived racial-ethnic inequities in COVID-19 healthcare were associated with less willingness to receive the COVID-19 vaccine among Black/African American and Native Hawaiian/Pacific Islander adults. © 2024 Lippincott Williams and Wilkins. All rights reserved.
Keywords: COVID-19; COVID-19 Vaccine; Ethnicity; Health inequities; Healthcare disparities; Healthcare system; Race; dept.pch; open-access; peer-reviewed

Intentions to create green start-ups for collection of unwanted drugs: an empirical study - Njoku, A.; Mouloudj, K.; Bouarar, A.C.; Evans, M.A.; Asanza, D.M.; Mouloudj, S.; Bouarar, A. (Sustainability (Switzerland), 2024)
Drug waste poses a real threat to human health and the environment. Therefore, recycling and sustainability scholars have recently sought practical solutions to the drug waste problem. Furthermore, several governments have made significant efforts to reduce the negative effects of waste, such as establishing programs to take back unwanted drugs (expired and unused) for recycling (i.e., drug reuse or drug redispersing). However, many of these programs have failed to achieve their goals. In this context, it is expected that creating green start-ups to collect unwanted drugs will contribute to solving this problem. Accordingly, this study aims to investigate the antecedents of intentions to create green start-ups for collecting unwanted drugs. To this end, the authors integrate start-up self-efficacy and drug waste collection-related knowledge constructs into the theory of planned behavior (TPB). Using a self-administered paper questionnaire and relying on a convenience sample, data were collected from 328 students in six Algerian universities. A hierarchical multiple regression was conducted to test the proposed study model. Theresults revealed that perceived behavioral control (PBC) (β = 0.187, p < 0.001), attitudes (β = 0.182, p = 0.002), start-up self-efficacy (β = 0.169, p = 0.001), drug waste collection-related knowledge (β = 0.161, p < 0.001), and subjective norms (β = 0.088, p < 0.05) have a positive significant effect on the intention to create a start-up to collect unwanted drugs. In conclusion, this paper contributes to reducing drug waste by investigating the drivers of intention to create green start-ups for collecting unwanted drugs. Therefore, our study is expected to provide valuable insights for hospitals, pharmacies, pharmaceutical manufacturers, environmental protection associations, and stakeholders interested in reverse logistics. © 2024 by the authors.
Keywords: circular economy; dept.pch; expired drugs; green entrepreneurship; medication disposal; peer-reviewed; pharmaceutical waste; recycling; sustainability; theory of planned behavior; unused drugs; waste management knowledge

Nursing student perceptions of racism and health disparities in the United States: A critical race theory perspective - Costa, M.; Griswold, M.K.; Canty, L. (Nursing Outlook, 2024)
Background: Limited research has been done on nursing students’ awareness of racial disparities and their readiness to address bias and racism in clinical practice. Purpose: This study investigated nursing students' perceptions of how racial disparities affect health outcomes, including maternal outcomes, in the United States. Methods: Interpretive description was used and supported by the critical race theory as a framework to guide the data collection, analysis, and interpretation to understand participants’ perceptions surrounding racism and health disparities. Discussion: Nurse educators should guide students to look beyond individual behavioral and risk factors and consider systemic issues as a leading contributors to health disparities. Conclusion: The most critical finding was the lack of participants’ understanding of systemic racism and its impact on health disparities. While they often attributed racial disparities to low socioeconomic status and lack of education, they did not understand the relationships between social determinants of health and systemic racism. © 2024
Keywords: Maternal health outcomes; Nursing education; Racial disparities; Student perceptions; dept.pch; peer-reviewed

Sleep duration and all-cause mortality among stroke survivors - Sawadogo, Wendemi; Adera, Tilahun; Burch, James B.; Alattar, Maha; Perera, Robert; Howard, Virginia J. (Journal of Stroke and Cerebrovascular Diseases, 2024)
Background Post stroke sleep duration could increase the risk of death. This study tested the hypothesis that inadequate sleep duration is associated with increased mortality among stroke survivors. Methods The REasons for Geographic And Racial Differences in Stroke (REGARDS), a national population-based longitudinal study, was the data source. Sleep duration was ascertained between 2013 and 2016 among stroke survivors who were subsequently followed up until death or censored on December 31, 2022. Sleep duration was estimated as the difference between wake-up time and bedtime to which was subtracted the time spent in bed without sleep. Cox proportional hazards regression models were employed to investigate the association between sleep duration and all-cause mortality adjusting for demographic factors, socioeconomic factors, behavioral factors, and co-morbidities. Results A total of 468 non-Hispanic Black and White stroke survivors were included in this analysis. The mean age was 76.3 years, 52.6% were females and 56.0% were non-Hispanic White individuals. The distribution of short (≤6 h), adequate (7.0–8.9 h), and long sleep (≥9 h) was 30.3%, 44.7%, and 25%, respectively. Over a mean follow-up of 5.0 years, 190 (40.6%) deaths occurred. Compared to stroke survivors with adequate sleep (7.0–8.9 h), stroke survivors with long sleep (≥9 h) were at increased risk of all-cause mortality (HR=1.46, 95% CI=1.01, 2.12). However, short sleep (≤6 h) was not significantly associated with an increased risk of all-cause mortality (HR=1.31, 95% CI=0.90, 1.91). Subgroup analyses indicated higher risk in the age <75 years, females, non-Hispanic Black individuals, and those living in the Stroke Belt region, but those differences were not statistically significant. Conclusion In this study of stroke survivors, 9 hours or more of sleep per day was associated with an increased risk of all-cause mortality. This finding suggests that excessive sleep duration may be a warning sign of poor life expectancy in stroke survivors.
Keywords: All-cause mortality; Cohort study; Sleep duration; Stroke survivors; dept.pch; peer-reviewed